Synthesis, Characterization and Thermodynamic Study of a Novel N-Functionalized Macrocycle And Its Metal Complexes - Bi, Jian-Hong; Chen, Li-Qin; Xu, Zhi-Qiang; Xie, Fu-Xin; Zhao, Xiang-Da; Ni, Shi-Sheng; Xu, Ji-De (Asian Journal of Chemistry, 2010)
A new N-carboxymethyl derivative of the tetraazamacrocyclic ligand LH4 (5,7,12,14-tetramethyl-1,4,8,11-tetraazamacrocyclo-tetradecane-N,N´,N"N''' -tetraacetic acid) and its complexes with Cu2+, Co2+, Ni2+, UO2+ and Th4+ have been synthesized and characterized by elemental analyses, UV, IR, 1H NMR spectra and X -ray powder diffraction. The stability constants of mononuclear complexes of LH4 with the ions above were determined at 35 ± 0.1, 45 ± 0.1 and 55 ± 0.1ºC in 0.5 mol L–1 KNO3 solution by means of potentiometric and computer fitting. The ΔH and ΔS of the coordination reactions in the solution were given.